2023
DOI: 10.3390/genes14061258
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Association Analysis of Growth and Backfat Traits in Large White Pigs

Abstract: The pig industry is significantly influenced by complex traits such as growth rate and fat deposition, which have substantial implications for economic returns. Over the years, remarkable genetic advancements have been achieved through intense artificial selection to enhance these traits in pigs. In this study, we aimed to investigate the genetic factors that contribute to growth efficiency and lean meat percentages in Large White pigs. Specifically, we focused on analyzing two key traits: age at 100 kg live w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the breeding of boars with outstanding production performance to serve as terminal male parents holds immense significance for the advancement of the pig industry. A body weight of 100 kg commonly serves as an indicator of the growth rate and feed efficiency of tested pigs [ 20 ], a threshold that also aligns with the optimal slaughter weight for lean pigs. In this study, we observed the age, backfat thickness, and eye muscle area of boars between the DD and PY groups when they weighted 100 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the breeding of boars with outstanding production performance to serve as terminal male parents holds immense significance for the advancement of the pig industry. A body weight of 100 kg commonly serves as an indicator of the growth rate and feed efficiency of tested pigs [ 20 ], a threshold that also aligns with the optimal slaughter weight for lean pigs. In this study, we observed the age, backfat thickness, and eye muscle area of boars between the DD and PY groups when they weighted 100 kg.…”
Section: Discussionmentioning
confidence: 99%
“…As globally recognized lean meat pig breeds, Duroc and Pietrain pigs have been utilized as terminal sires in pig hybrid systems (Pedersen et al., 2019). Owing to their similar breeding directions, both Duroc and Pietrain pigs demonstrate a rapid growth rate and a high lean meat percentage as a result of long‐term artificial selection (Zhou et al., 2023), making them natural models for exploring phenotypic convergence and adaptive evolution (Rubin et al., 2012). In recent years, the identification of parallel selection signatures between populations has emerged as a pivotal focus in the field of population genetics, propelled by advancements in genome sequencing technology and statistical genomics.…”
Section: Fields Pietrain Duroc European Wild Boar Overallmentioning
confidence: 99%